Employing structural equation modeling to discern teachers’ perspectives and their embrace of the Metaverse within the classroom setting - Mendonça, Yuri V. S.; Vinueza-Naranjo, Paola G.; Pinto, Diego Costa (Frontiers in Education, 2024)
The rise of smart learning environments and the transformative potential of the Metaverse are increasingly evident across various sectors, particularly in education. While substantial attention has been directed towards student engagement within the Metaverse, the evolution of teaching methodologies enabled by this technology remains under examined. This study investigates the influence of teachers' prior experience with technology on their willingness to adopt the Metaverse in diverse educational contexts. Utilizing a sample of 311 educators from the Brazilian Amazon, Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to validate the theoretical model. The findings emphasize the significant relationship between previous technological experiences, the mediating role of social influence in adoption, and performance expectations. Furthermore, the results underscore the pivotal role of technological engagement in shaping educators' perceptions and their readiness to adopt emerging innovations, such as the Metaverse.